Cassava rapid stem multiplication tunnel: Construction manual - Delaquis, Erik; Newby, Jonathan Craig; Malik, Al Imran; Youabee, Laothao; Oudthachit, Saythong; Escobar Pérez, Roosevelt Humberto (2023)
This manual will teach you how to build a rapid stem multiplication tunnel based on CIAT’s experiences in Colombia and Lao PDR . These tunnels have been developed by CIAT and tested in South America and Asia, proving to be practical solutions for rapid production of clean planting materials .